(untitled) (Research, Society and Development, 2024)
In late 2019, the Chinese city of Wuhan saw an exponential increase in cases of pneumonia caused by a new virus called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Over the past four years, millions of people around the world have died due to the clinic symptoms caused by this severe infection. Most cases are mild and asymptomatic, however, due to some comorbidities, such as elderliness, some individuals have developed a more severe form of the disease. This research aims to evaluate lung function in elderly patients who were affected by COVID-19. For this purpose, 30 patients attending a physiotherapy service in a northeastern capital city were conveniently recruited. The elderly were divided into two groups, the study group (SG) and the control group (CG), consisting of those previously infected with SARS-CoV-2 and those not affected by the disease, respectively. The data collected were analyzed using an α value of p < 0.05 for statistical significance. The mean age of individuals with COVID-19 and without COVID-19 did not differ significantly, characterizing a homogeneous sample. With regard to vital signs, patients belonging to the SG had a higher tachycardia. In spirometry, the Tiffeneau Index (FEV1/FVC) showed p = 0.020, in which the SG resulted in an average of 88.94 ± 10.33% and the CG, 72.67 ± 21.09%, indicating a greater impairment of airflow in the SG.